(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Mechanical ventilation is widely used in intensive care units. However, ventilator-related errors and mismanagement can lead to severe complications. Nurses play a pivotal role in monitoring and managing ventilated patients, making their knowledge and practices crucial to patient safety. Objective: This study aimed to determine awareness and practices of nurses regarding mechanical ventilation errors. Methodology: A descriptive cross-sectional study was conducted in the intensive care units of two tertiary care hospitals: Khyber Teaching Hospital and Hayatabad Medical Complex, Peshawar. A total of 92 registered nurses were selected through proportionate stratified convenience sampling technique. Data were collected using a structured self-administered questionnaire. Data were analyzed using SPSS version 27. Results: The findings revealed that 83% of the participants had good knowledge regarding ventilator management, while 17% demonstrated poor understanding. Nurses displayed satisfactory awareness of basic ventilator concepts such as Fraction of Inspired oxygen and tidal volume, but deficiencies were noted in alarm management, flow rate adjustment, and weaning procedures. A positive correlation was observed between knowledge and practices, indicating that improved understanding contributed to safer clinical behaviors. Conclusion: The study concludes that nurses working in tertiary care hospitals of Peshawar generally possess good knowledge and satisfactory practices regarding ventilator management. However, gaps persist in technical areas that may predispose patients to ventilator-related errors. Regular in-service education, simulation-based training, and competency assessments are recommended to strengthen practical skills and ensure the safe management of mechanically ventilated patients.